Selection of 3D Printer for racing car spoilers using Entropy - CRADIS model - Ranjan, Rajeev; Rajak, Sonu; Chatterjee, Prasenjit (Vojnotehnički glasnik / Military Technical Courier, 2026)
Introduction/purpose: This study aims to identify the most suitable 3D printer for manufacturing racing car spoilers.Methods: Sixteen different 3D printing machines are evaluated based on eight selection criteria. The criteria weights are determined using the Entropy method, while Compromise Ranking of Alternatives from Distance to Ideal Solution (CRADIS) method is applied to rank the machines and identify the best option for spoiler production. Sensitivity analysis is conducted using various methods to validate the results.  Results: Ultimaker 2 is identified as the most suitable 3D printer, followed by Delta Non-Turbo WASP 2040, while UP Plus 2 ranks as the least favorable.Conclusion: By using the Entropy and CRADIS method, Ultimaker 2, is identified as the best-performing 3D printer, followed by Delta Non-Turbo WASP 2040, while UP Plus 2 received the lowest ranking. Various MCDM methods are applied for performance comparison and sensitivity analysis, with the Spearman Rank Correlation Coefficient applied to assess the correlation between different MCDM methods.
Keywords: 3D Printing; Multi criteria decision making; Entropy; CRADIS; sensitivity analysis; Additive manufacturing